Fuel economy valuation and preferences of Indian two-wheeler buyers. (20th April 2021) - Bansal, Prateek; Dua, Rubal; Krueger, Rico; Graham, Daniel J.
Abstract: India has experienced exponential growth in sales of two-wheelers due to their high fuel economy and easy manoeuvrability in congested traffic conditions. Understanding Indian consumers' valuation of fuel economy while purchasing a two-wheeler is crucial to evaluate whether Indian two-wheeler buyers are myopic with regards to future fuel costs. However currently, there exists no quantification of the value that Indian two-wheeler buyers ascribe to fuel economy. We address this gap in the literature by analyzing revealed preference survey data from more than 8000 respondents across India, who purchased a new two-wheeler in 2018. Discrete choice models, including standard conditional logit and flexible mixed logit, are used to infer estimates of the discount rate that Indian consumers apply to obtain the present value of future operating cost at the time of two-wheeler purchase. The results of conditional logit indicate that the annual discount rate is below 10% for Indian two-wheeler buyers with monthly household incomes above 15, 000 rupees (∼US215 in 2018; ∼73% of the sample). Mixed logit suggests substantial heterogeneity in discount rates across respondents at a given income level. The median of the mixing distribution is close to the conditional logit estimates, which leads to a conclusion that an average Indian two-wheeler buyer ascribes a high value to future fuel cost savings. Besides, our analysis provides various insights into Indian consumers' preferences. For instance, style/looks, fuel economy, comfort, and brand (in decreasing order) are the top four factors that influence two-wheeler purchase decisions of Indian consumers. Highlights: Estimate fuel economy valuation for Indian two-wheeler (2 W) buyers. Use revealed preference survey data of 8159 2 W buyers across India. Annual discount rate is below 10% for most of the Indian 2 W buyers. Indian 2 W buyers are not myopic about future fuel costs. Style, fuel economy, comfort, and brand are top 4 factors in 2 W purchase decisions.